Optimizing Students' Speaking Ability Using Padlet in Giving Opinion at Indonesian Junior High School: A Classroom Action Research - Aini Laily Naja; Dangin Dangin (Linguistic, English Education and Art (LEEA) Journal, 2024)
This study aims to determine the impact and perceptions of students in English speaking skills, especially giving opinions via Padlet. This study was conducted at Indonesian Junior High School with 20 students as respondents. Data has been obtained using qualitative descriptive methods. Qualitative data has been obtained from interviews, pre-tests, and post-test. To solve the problem, the study has carried out Class Action Research (CAR) which consists of planning, acting, observing, and reflecting. The test only given to students. The result of the study showed that Paddlet has positive impact on students’ speaking ability. It reveals increase about 21.15% from the pre-test. It can be concluded that optimizing students’ speaking ability using Padlet in giving opinion can be an alternative of effective teaching ways. Keywords: CAR, Padlet, Speaking Ability